2009
DOI: 10.1002/mus.21352
|View full text |Cite
|
Sign up to set email alerts
|

DMPK protein isoforms are differentially expressed in myogenic and neural cell lineages

Abstract: Myotonic dystrophy type 1 (DM1) is a neuromuscular disorder caused by an unstable (CTG . CAG)n segment in the 3' untranslated region of the myotonic dystrophy protein kinase (DMPK) gene. It is commonly accepted that DMPK mRNA-based toxicity is the main contributor to DM1 manifestations; however, not much is known about the significance of the DMPK protein. To appreciate its normal and possible pathobiological role, we analyzed the patterns of DMPK splice isoform expression in mouse tissues. Long membrane-ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…DMPK at protein level has also been identified in several brain regions (van der Ven et al, 1993) both in neurons and glia. Interestingly astrocytes from brain cortex show higher DMPK levels compared with neurons (Oude Ophuis et al, 2009a). DMPK transcripts and protein products are also detected in fetal eyes, adult retina, corneal epithelia and optic nerve (Winchester et al, 1999).…”
Section: Tissue Distribution Of Dmpkmentioning
confidence: 98%
See 4 more Smart Citations
“…DMPK at protein level has also been identified in several brain regions (van der Ven et al, 1993) both in neurons and glia. Interestingly astrocytes from brain cortex show higher DMPK levels compared with neurons (Oude Ophuis et al, 2009a). DMPK transcripts and protein products are also detected in fetal eyes, adult retina, corneal epithelia and optic nerve (Winchester et al, 1999).…”
Section: Tissue Distribution Of Dmpkmentioning
confidence: 98%
“…Interestingly, both longand short-isoforms are expressed in diverse brain regions (Oude Ophuis et al, 2009a). Other reports have demonstrated that the four different ~74-kDa full-length DMPK isoforms are present in heart, skeletal muscle and brain, in contrast to the two C-terminally truncated ~68-kDa isoforms that are restricted to smooth muscle and to a lesser extent at heart (Groenen et al, 2000).…”
Section: Tissue Distribution Of Dmpkmentioning
confidence: 99%
See 3 more Smart Citations